2010
DOI: 10.1540/jsmr.46.1
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal hypersensitivity to acid in patients with functional dyspepsia-pathogenesis and evaluation

Abstract: Functional dyspepsia (FD) is a subcategory of the functional gastrointestinal disorders according to the Rome III classification of functional gastroduodenal disorders. FD is characterized by the presence of symptoms that are believed to be associated with gastroduodenal lesions, particularly epigastric pain or burning, postprandial fullness, or early satiation, without the evidence of organic disease likely to explain the onset of these symptoms. Generally, multiple factors are considered to be involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…Although gastroscopy was not performed on any of our cases, we do not believe anorexia occurred from gastroduodenal ulcers, as it spontaneously resolved after pirfenidone discontinuation. PPIs and H2RAs do not directly activate gastric motility; however, they are known to improve postprandial fullness and early satiation observed in functional dyspepsia without organic disease [22] through attenuating duodenal hypersensitivity to acids [23]. It is reported that PPI monotherapy improves dysmotility-like symptoms significantly better than that of H2RAs plus mosapride in functional dyspepsia [24].…”
Section: Discussionmentioning
confidence: 99%
“…Although gastroscopy was not performed on any of our cases, we do not believe anorexia occurred from gastroduodenal ulcers, as it spontaneously resolved after pirfenidone discontinuation. PPIs and H2RAs do not directly activate gastric motility; however, they are known to improve postprandial fullness and early satiation observed in functional dyspepsia without organic disease [22] through attenuating duodenal hypersensitivity to acids [23]. It is reported that PPI monotherapy improves dysmotility-like symptoms significantly better than that of H2RAs plus mosapride in functional dyspepsia [24].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, just infusing a small amount (0.1 mol/L) of acid into the stomach can aggravate indigestion in most people [ 28 ]. In addition, acidification of the duodenum exacerbates dyspeptic symptoms by inducing proximal gastric relaxation and inhibiting gastric accommodation to a meal [ 29 ]. In one animal study, duodenal acidification-induced gastric hypersensitivity could be the cause of dyspepsia in patients with IBS and serotonin 5-HT3 receptors play a key role [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supporting the stomach rather than the duodenum as the main source of symptoms includes the rapid resolution of symptoms when water is ingested (11,19,20), and the endoscopic observation of pooled capsaicin in the gastric corpus but not beyond after oral ingestion (11). However, with the present understanding of the pathophysiology of FD, this may not be of prime importance, as both gastric and duodenal mechanisms are probably involved (3,56,57). Another potential confounder is the open capsaicin dose titration on study days 2 and 3, whereas the titration on day 1 was nocebo‐controlled and visually blinded.…”
Section: Discussionmentioning
confidence: 99%